Exercise in People With Cancer: A Spotlight on Energy Regulation and Cachexia - Allan, Jessica; Buss, Linda A.; Draper, Nick; Currie, Margaret J. (Frontiers in Physiology, 2022)
Exercise is increasingly becoming a standard of cancer care, with well-documented benefits for patients including improved mental wellbeing and reduced treatment-related side effects. However, important gaps in knowledge remain about how to optimise exercise prescription for people with cancer. Importantly, it remains unclear how exercise affects the progression of cancer cachexia (a wasting disease stemming from energy imbalance, and a common manifestation of advanced malignant disease), particularly once the condition has already developed. It was recently suggested that the anti-tumour effect of exercise might come from improved energetic capacity. Here, we highlight the possible effect of exercise on energetic capacity and energy regulation in the context of cancer, and how this might affect the progression of cancer cachexia. We suggest that due to the additional energy demand caused by the tumour and associated systemic inflammation, overreaching may occur more easily in people with cancer. Importantly, this could result in impaired anti-tumour immunity and/or the exacerbation of cancer cachexia. This highlights the importance of individualised exercise programs for people with cancer, with special consideration for the regulation of energy balance, ongoing monitoring and possible nutritional supplementation to support the increased energy demand caused by exercise.